Firstly, you need to set the equation to 0. To do that, subtract both sides by 25:
.
Next, we can complete the square. But first, what two terms have a product of -21x^2 and a sum of 4x? That would be 7x and -3x. Replace 4x in the equation with 7x - 3x:
![x^2 +7x-3x-21=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/lrd5c5eqlms6d97jnbbnkmj8ok49ng2ly1.png)
Next, factor x^2 + 7x and -3x - 21 separately. Make sure that they both have the same quantity on the inside:
![x(x+7)-3(x+7)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/30cywcmvd68f90buu9erxfvgqotw13wld1.png)
Now you can rewrite the equation as
![(x-3)(x+7)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/uzifrdqfon5a7fg09j8bcekrebebrof6ex.png)
Now using zero product property, solve for x:
![x-3=0\\ x=3\\ \\ x+7=0\\ x=-7](https://img.qammunity.org/2019/formulas/mathematics/high-school/u7cpp6v23rhbijg12f7nbc73bm0zc2spbz.png)
In short, your answer is A. x = 3 or x = -7.